2019
DOI: 10.1002/adfm.201905115
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial‐Induction of a Transplantable Angiosome

Abstract: Creating transplantable vascular networks (angiosomes) that are fed and drained by vessels large enough to be surgically reconnected is key to harnessing the potential of regenerative medicine and advancing reconstructive surgical techniques. Currently, the only way to create a new angiosome is nontrivial and involves pressurizing a vein graft by its surgical attachment to an artery forming an arteriovenous loop (AVL). Material induction of a venous angiosome is reported, by placement of a 3D printed microporo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Since prior work had indicated that polymers could not elicit venous sprouting [ 14 ], here we examined the sprouting capacity of other inorganic materials that are in use clinically or have been proposed as bone graft substitutes. Analysis of the XRD patterns ( Figure 7 A) revealed an amorphous cementitious phase of magnesium phosphate, since only peaks characteristic of unreacted magnesium oxide at 43° and 62° 2θ were apparent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since prior work had indicated that polymers could not elicit venous sprouting [ 14 ], here we examined the sprouting capacity of other inorganic materials that are in use clinically or have been proposed as bone graft substitutes. Analysis of the XRD patterns ( Figure 7 A) revealed an amorphous cementitious phase of magnesium phosphate, since only peaks characteristic of unreacted magnesium oxide at 43° and 62° 2θ were apparent.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1β is responsible for crosstalk between macrophages and smooth muscle cells and augments secretion of VEGF in both cell types [ 33 ]. In further support of the role of inflammatory processes, our laboratory previously observed that wrapping a silicone membrane around the outside of the implant prevented any luminal sprouting [ 14 ]. We tentatively attribute this to the prevention of phagocyte infiltration [ 41 ], since F4/80-positive cells were mainly observed in the outer portion of the scaffold initially ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation